Comparative Effectiveness of Regimens for Drug-Susceptible Tuberculous Meningitis in Children and Adolescents: A Systematic Review and Aggregate-Level Data Meta-Analysis. (9th April 2022) - Sulis, Giorgia; Tavaziva, Gamuchirai; Gore, Genevieve; Benedetti, Andrea; Solomons, Regan; van Toorn, Ronald; Thee, Stephanie; Day, Jeremy; Verkuijl, Sabine; Brands, Annemieke; Viney, Kerri; Masini, Tiziana; et al.
Abstract: Background: Before August 2021, the only regimen recommended by the World Health Organization (WHO) to treat pediatric drug-susceptible tuberculous meningitis was a 12-month regimen consisting of isoniazid, rifampicin, ethambutol, and pyrazinamide (2HRZE/10HR). The comparative effectiveness of shorter regimens is unknown. Methods: To inform a WHO guideline update, we undertook a systematic review and meta-analysis to evaluate outcomes from regimens of 6- to less than 12-months' duration that included, at a minimum, isoniazid, rifampicin, and pyrazinamide. We included studies that applied rigorous diagnostic criteria and reported outcomes for ≥10 children or adolescents. Using generalized linear mixed models, we estimated the random effects pooled proportions of patients with key outcomes. Results: Of 7 included studies, none compared regimens head-to-head. Three studies (724 patients) used a 6-month intensive regimen, which includes isoniazid and rifampicin at higher doses, pyrazinamide, and ethionamide instead of ethambutol (6HRZEto). Outcomes for this versus the 12-month regimen (282 patients, 3 studies) were, respectively, as follows: death, 5.5% (95% confidence interval [CI], 2.1%–13.4%) vs 23.9% (95% CI, 17.5%–31.7%); treatment success (survival with or without sequelae), 94.6% (95% CI, 73.9%–99.1%) vs 75.4% (95% CI, 68.7%–81.1%); and neurological sequelae among survivors, 66.0% (95% CI, 55.3%–75.3%) vs 36.3% (95% CI, 30.1%–43.0%). Relapse did not occur among 148 patients followed-up for 2 years after completing the 6-month intensive regimen. Conclusions: Our findings are limited by the small number of studies and substantial potential for confounding. Nonetheless, the 6HRZEto regimen was associated with high treatment success and is now recommended by WHO as an alternative to the 12-month regimen. Abstract : Compared with a 12-month regimen consisting of isoniazid, rifampicin, pyrazinamide, and ethambutol (2HRZE/10HR), an intensive 6-month regimen—which replaces ethambutol with ethionamide (6HRZEto)—is associated with lower mortality but more frequent neurological sequelae among survivors of pediatric tuberculous meningitis.